2010
DOI: 10.1080/10911350903269880
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Housing: Exploring the Impact of Medical and Substance Abuse Services on Housing Attainment for Chronically Homeless Street Dwellers

Abstract: This mixed-methods study addresses transitions out of homelessness associated with medical and substance abuse service use for a unique cohort of 174 chronically homeless street dwellers at risk of death. Multi-nominal and survival analyses indicate that highrisk women, white street dwellers, older individuals, and those with health insurance coverage had greater odds of leaving the streets. Thouh high-risk street dwellers used health services extensively, medical and substance abuse treatments did not impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…With the goal of providing safe locations for individuals to continue medical recovery, medical respite (alternately called intermediate or convalescent care) has resulted in the improved health and reduced healthcare utilisation and costs for general populations of people experiencing homelessness (Doran et al, ). Though research on the impact of respite care has found mixed results regarding the mortality risk of respite patients versus comparison groups (Meschede, ; Sadowski & Buchanan, ; van Laere, de Wit, & Klazinga, ), medical respite patients have been found to experience improvements in quality of life, medication stabilisation, access to health and community care, insurance, income and housing, as well as reductions in substance use following treatment (Bauer, Moughamian, Viloria, & Schneidermann, ; Podymow, Turnbull, Tadic, & Muckle, ; Sadowski & Buchanan, ; Zerger, ). In addition, medical respite programmes have demonstrated reduced future hospital admissions, inpatient days and hospital readmissions among homeless patients, resulting in significant healthcare system cost savings (Basu, Kee, Buchanan, & Sadowski, ; Buchanan, Doblin, Sai, & Garcia, ).…”
Section: Discussionmentioning
confidence: 99%
“…With the goal of providing safe locations for individuals to continue medical recovery, medical respite (alternately called intermediate or convalescent care) has resulted in the improved health and reduced healthcare utilisation and costs for general populations of people experiencing homelessness (Doran et al, ). Though research on the impact of respite care has found mixed results regarding the mortality risk of respite patients versus comparison groups (Meschede, ; Sadowski & Buchanan, ; van Laere, de Wit, & Klazinga, ), medical respite patients have been found to experience improvements in quality of life, medication stabilisation, access to health and community care, insurance, income and housing, as well as reductions in substance use following treatment (Bauer, Moughamian, Viloria, & Schneidermann, ; Podymow, Turnbull, Tadic, & Muckle, ; Sadowski & Buchanan, ; Zerger, ). In addition, medical respite programmes have demonstrated reduced future hospital admissions, inpatient days and hospital readmissions among homeless patients, resulting in significant healthcare system cost savings (Basu, Kee, Buchanan, & Sadowski, ; Buchanan, Doblin, Sai, & Garcia, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 14 have shown that a variety of interventions do not lead to improvements in housing status. Our data indicate that, for patients receiving the Pathway intervention, the proportion of people who return to the streets is reduced.…”
Section: Discussionmentioning
confidence: 95%
“…A large study conducted in Massachusetts demonstrated that homeless idu were more likely to enter detoxification and residential treatment programs but were half as likely to access mmt over the four-year study period (Lundgren et al 2003). These short-term programs often do not lead to improved long-term housing outcomes due to a lack of integration between substance abuse treatment and housing services, insufficient or unacceptable housing options and other gaps in the continuum of care (Meschede 2010).…”
Section: Barriers To Housingmentioning
confidence: 99%